Characterization and ontogeny of a novel lymphoid follicle inducer cell during development of the bursa of Fabricius - Szőcs, Emőke; Balic, Adam; Soós, Ádám; Halasy, Viktória; Nagy, Nándor (Frontiers in Immunology, 2024)
The avian bursa of Fabricius (BF) is a primary lymphoid organ, where B-cell development occurs within bursal follicles of epithelial origin. During embryogenesis the epithelial anlage of the BF emerges as a diverticulum of the cloaca surrounded by undifferentiated tail bud mesenchyme. While it is believed that the epithelial-mesenchymal BF primordium provides a selective microenvironment for developing B cells, the initial events inducing lymphoid follicle formation are not fully elucidated. Using wild type and CSF1R-eGFP transgenic chick embryos, we find that separate B cell, macrophage and dendritic cell precursors enter the BF mesenchyme, migrate to the surface epithelium, and colonize the lymphoid follicle buds. Detailed immunocytochemical characterization revealed a novel EIV-E12+ blood-borne cell type, colonizing the surface epithelium of the BF rudiment before the entry of myeloid and lymphoid lineages and the appearance of this cell type coincides with the onset of follicle bud formation. Chick-duck chimeras and chick-quail tissue recombination experiments suggest that EIV-E12+ cells represent a transient lymphoid inducer cell population. They are not dendritic or B cells precursors, and they are capable of follicle bud induction in both dendritic cell-and B cell-depleted bursae.